A pioneer experience in Malaysia on In-house Radio-labelling of 131I-rituximab in the treatment of Non-Hodgkin's Lymphoma and a case report of high dose 131I-rituximab-BEAM conditioning autologous transplant. (October 2016) - Kuan, Jew Win; Law, Chiong Soon; Wong, Xiang Qi; Ko, Ching Tiong; Awang, Zool Hilmi; Chew, Lee Ping; Chang, Kian Meng
Abstract: Radioimmunotherapy is an established treatment modality in Non-Hodgkin's lymphoma. The only two commercially available radioimmunotherapies – 90 Y-ibritumomab tiuxetan is expensive and 131 I-tositumomab has been discontinued from commercial production. In resource limited environment, self-labelling 131 I-rituximab might be the only viable practical option. We reported our pioneer experience in Malaysia on self-labelling 131 I-rituximab, substituting autologous haematopoietic stem cell transplantation (HSCT) and a patient, the first reported case, received high dose 131 I-rituximab (6000 MBq/163 mCi) combined with BEAM conditioning for autologous HSCT. Highlights: Usual dose: Day 0 (dosimetry) – 5 mCi, Day 7 (therapeutic) 0.75 Gy to whole body. High dose: 6000 MBq (163 mCi) on Day − 18, BEAM conditioning starts on Day − 8. Self-labelled 131 I-rituximab is a viable treatment in resource limited environment. 131 I-rituximab may substitute autologous transplant. High dose 131 I-rituximab-BEAM is a feasible conditioning regime.